Application of Metal-Based Nanozymes in Inflammatory Disease: A Review - Li, Ruifeng; Hou, Xinyue; Li, Lingrui; Guo, Jiancheng; Jiang, Wei; Shang, Wenjun (Frontiers in Bioengineering and Biotechnology, 2022)
Reactive oxygen species (ROS) are metabolites of normal cells in organisms, and normal levels of ROS in cells are important for maintaining cell signaling and other intracellular functions. However, excessive inflammation and ischemia-reperfusion can cause imbalance of tissue redox balance, and oxidative stress occurs in tissue, resulting in a large amount of ROS, causing direct damage to tissue. The production of many diseases is associated with excess ROS, such as: stroke, sepsis, alzheimer's disease, parkinson's disease, etc. In recent years, with the rapid development of nanomedicine, nanomaterials have been widely used in the effective treatment of various inflammatory diseases due to their superior physical and chemical properties. In this review, we summarize the application of some representative nanozyme in inflammatory diseases. In addition, we discuss the application of various novel nanomaterials for further therapy and the prospects of using nanoparticles as biomedical materials.